The Influence of Tax System Perception, Tax Justice, Tax Rate, Tax Audit, Discrimination on Tax Embroidery Behaviour - Hamilah, Hamilah; Lydia, Lydia; Henni, Henni; Gusmiarni, Gusmiarni; Reschiwati, Reschiwati (Center for Risk Management & Sustainability and RSF Press, 2022)
This study intends to define and analyze the perceived effects of the tax system, tax justice, tax rates, tax audits, and discrimination on tax evasion behavior. Tax Evasion is the dependent variable here. In contrast, the independent variables are the perception of the taxation system, tax justice, tax rates, tax audit, and discrimination. The study has a population consisting of individual taxpayers enlisted at the Depok Sawangan Tax Office. The convenience sampling technique is used to select respondents. This research uses a quantitative method to obtain data from questionnaire instruments. The results of data analysis have been done by utilizing Structural Equation Modeling (SEM). Tax justice and tax audit had a significant effect on tax evasion behavior, while tax rates, taxation systems, and tax discrimination had no significant effect on tax evasion behavior, according to the study's findings.